4E (Energy, Exergy, Economic, and Environment) examination of a small LFR solar water heater: An experimental and numerical study. (October 2021) - Said, Zafar; Ghodbane, Mokhtar; Tiwari, Arun Kumar; Ali, Hafiz Muhammad; Boumeddane, Boussad; Ali, Ziad M.
Abstract: An experimental and numerical study on the solar water heater is carried out in Blida area, Algeria during winter in this work. Numerical results are confirmed by experimental results, where the numerical results are presented in two forms: Numerical solution based on estimated equations of climatic data and numerical solution based on actual values of weather data. Finite difference method was used to analyze and simplify energy balance equations. Results obtained showed a significant convergence between experimental and numerical results, where optical efficiency has passed 42.65 %, while the highest value for thermal efficiency was 29.212 % on February 22, 2015, while its average exergy efficiency for February 19, 2015 is 1.81 %. Experimentally, the maximum value of hot water temperature reached 352 K on February 19, 2015. As for the volume of water heated by the studied collector, it is 0.4 m 3 /day. The system performance is 19.75%, the equivalent of an electrical capacity of 545.68 kWh. Economically, the LFR reflector cost is 378.87 $, where this cost can be recovered after sixteen years of the first use, as the cost of heat generation is 0.043 $/kWh. Environmentally, the CO2 mitigation is 247.14 kg. Additionally, this reflector will provide the equivalent of 127.47 m 3 of Liquefied natural gas. Highlights: A small linear Fresnel reflector designed to produce hot water. The optical efficiency exceeded 42.65 %, the thermal efficiency reached 29.212% and the average exergy efficiency is 1.81%. The daily production of hot water is 0.4 m 3 . The cost recovery period is 16 years and the cost heat generation is 0.043 $/kWh. CO2 mitigation is 247.14 kg. Graphical abstract: Image 1